Real clinical experience after one year of treatment with tolvaptan in patients with autosomal dominant polycystic kidney disease - Naranjo, Javier; Borrego, Francisco; Rocha, José Luis; Salgueira, Mercedes; Martín-Gomez, Maria Adoración; Orellana, Cristhian; Morales, Ana; Vallejo, Fernando; Hidalgo, Pilar; Rodríguez, Francisca; Garófano, Remedios; González, Isabel; et al. (Frontiers in Medicine, 2022)
ABSTRACT BACKGROUND Tolvaptan (TV) is the first vasopressin-receptor antagonist approved for the treatment of autosomal dominant polycystic kidney disease (ADPKD). There are no publications reporting experience with TV in real clinical practice during the first year of treatment. METHODS Prospective study of an initial cohort of 220 rapidly progressing patients treated with TV for 12 months. Tolerability of TV, evolution of estimated glomerular filtration rate (eGFR), analytical parameters and blood pressure were analyzed. RESULTS A total of 163 patients (78.2%) received TV for one year. The main causes of treatment withdrawal were the aquaretic effects (11%), eGFR deterioration (5%) and hepatic toxicity (2.3%). eGFR decreased significantly after one month of treatment without further changes. The decrease in eGFR at the first one month was higher in patients with an initially higher eGFR. The eGFR drop during the first year of treatment with TV was lower than that presented by patients in the 2 years prior TV treatment (-1.7±7.6 vs. -4.4±4.8 mL/min, p=0.003). Serum sodium and uric acid concentrations increased, and morning urinary osmolality decreased in the first month, with no further changes. Blood pressure decreased significantly without changes in antihypertensive medication. CONCLUSIONS. TV treatment is well tolerated by most patients. Liver toxicity is very rare and self-limited. TV reduces eGFR in the first month without showing further changes during the first year of treatment. Patients with a higher starting eGFR will suffer a greater initial drop, with later recovery. We suggest using the eGFR observed after a month of treatment as the reference for future comparisons and for calculating the rate of eGFR decline in patients undergoing TV treatment.